2008
DOI: 10.1017/s1751731107001036
|View full text |Cite
|
Sign up to set email alerts
|

Tick susceptibility and its effects on growth performance and carcass characteristics of Nguni, Bonsmara and Angus steers raised on natural pasture

Abstract: The objective of the current study was to compare tick loads, growth and carcass characteristics of dipped and non-dipped Nguni, Bonsmara and Angus steers raised on natural pasture. One hundred 7-month-old castrated weaners were kept at the University of Fort Hare Farm for 12 months. There were 30 weaners each of Angus and Bonsmara, and 40 weaners of the Nguni breed. Half the Bonsmara, Angus and 14 Nguni weaners were dipped every fortnight. The rest were not dipped. Monthly weights and tick counts under the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
72
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 29 publications
14
72
0
Order By: Relevance
“…Assessment of meat production in the communal areas should include meat acceptability. Previous studies showed that there were no differences between beef from Nguni and Bonsmara steers in terms of their physical and histological meat quality characteristics (Muchenje et al, 2008a); while the Nguni had low tick loads and the Bonsmara had better carcass characteristics under natural grazing (Muchenje et al, 2008b), the Bonsmara steers were more stress-responsive at slaughter than the Nguni steers (Ndlovu et al, 2008). These studies however did not include sensory evaluation and its relationship with physical meat attributes.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Assessment of meat production in the communal areas should include meat acceptability. Previous studies showed that there were no differences between beef from Nguni and Bonsmara steers in terms of their physical and histological meat quality characteristics (Muchenje et al, 2008a); while the Nguni had low tick loads and the Bonsmara had better carcass characteristics under natural grazing (Muchenje et al, 2008b), the Bonsmara steers were more stress-responsive at slaughter than the Nguni steers (Ndlovu et al, 2008). These studies however did not include sensory evaluation and its relationship with physical meat attributes.…”
Section: Introductionmentioning
confidence: 97%
“…The indigenous Nguni cattle breed of South Africa is small to medium sized, but adapted to harsh environments Muchenje et al, 2008a and2008b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nguni breed has been shown to be resistant to nematodes (Xhomfulana et al, 2009), ticks (Muchenje et al, 2008a) and tick-borne diseases (Marufu et al, 2010), tolerant to pre-slaughter stress (Ndlovu et al, 2008;Muchenje et al, 2009) and produce meat of comparable quality to established beef breeds under rangeland conditions (Muchenje et al, 2008b). Although rangeland energy and mineral supplies in the dry seasons are sufficient to meet the production requirements of Nguni cattle (Mapiye et al, 2010a), they lose -E-mail: cmapiye@yahoo.co.uk body condition and weight in the same season as a consequence of limited protein supply (Mapiye et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, indigenous cattle breeds such as the Afrikaner, Drakensberger and Nguni breeds have made major contributions to livestock production because of their ability to adapt and produce in different systems (Muchenje et al, 2008;Beffa et al, 2009;Matjuda et al, 2014 ). The Afrikaner, Drakensberger, Nguni and Tuli cattle breeds have a long history of participation in animal recording and have an average complete pedigree recording in the first generation varying from 88.5% for the Nguni to 92.5% for the Afrikaner (Table 2).…”
mentioning
confidence: 99%